Women's Experiences of the Justice System - Morris, J (Victoria University of Wellington Law Review, 1997)
This article considers the impact of gender upon women's experiences of the New Zealand justice system, as lawyers and clients. As well as summarising study and survey material, it draws upon information provided to the Law Commission in the course of its project on Women's Acces to Justice: He Putanga mo nga Wahine ki te Tika. It concludes that women are still significantly disadvantaged by the justice system as a result of their gender and that there is an ongoing need for debate and consideration of these issues if women's access to justice is to be improved.